The Effect of Interactive Learning Media on Students’ Motivation in Writing “My Experience” Stories among Sixth-Grade Students - Yusniar, Yusniar; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This research was motivated by the low level of student motivation in story writing activities at SD Negeri 096 Manyabar, Mandailing Natal Regency. Observational data revealed that teachers still tend to use conventional methods and have not yet optimally utilized interactive learning media. As a result, the learning process becomes less engaging and students show passive behavior, particularly in writing stories with the theme “My Experience.” Writing is a productive skill in Indonesian language learning that requires motivational stimuli so students can creatively express their ideas and personal experiences. This study aims to examine the influence of interactive learning media on student motivation in writing “My Experience” stories. The research employed a quantitative approach using a quasi-experimental method. The sample consisted of 30 sixth-grade students at SD Negeri 096 Manyabar in the 2025/2026 academic year. Data were collected through observation, a motivation questionnaire, and documentation of students’ written work. The instruments were tested for validity and reliability before use. The results showed that the use of interactive learning media had a positive effect on students’ learning motivation. The average motivation score increased to 67.23 after the implementation of the media. A total of 86.7% of the students fell into the high motivation category. Furthermore, students' perceptions of the media averaged 59.27, indicating that they felt motivated and supported during the learning process. The increase in motivation was also reflected in students’ active participation in composing, writing, and presenting their personal experience stories. It can be concluded that interactive learning media not only assist teachers in delivering material but also serve as a motivational tool that enhances the attractiveness of the learning process and stimulates students’ creativity in writing